Consequential differences in perspectives and practices concerning children with developmental language disorders: an integrative review. Issue 4 (4th April 2019) - Gallagher, Aoife L.; Murphy, Carol‐Anne; Conway, Paul; Perry, Alison
Abstract: Background: Inter‐professional collaboration (IPC) has been recommended for many years as a means by which the needs of children with developmental language disorders (DLD) can be met at school. However, effective IPC remains difficult to achieve and our knowledge of how to support it is limited. A shared understanding between those involved has been identified as critical to IPC. Aims: To examine the literature, as one source of data, for evidence of a shared understanding between the fields of speech and language therapy (SLT) and education about children with DLD and how such needs can best be met at school. Methods & Procedures: An integrative review of the literature was undertaken. A systematic search of the published, peer‐reviewed literature (between 2006 and 2016) was conducted for empirical and theoretical papers and a manual search was undertaken to obtain a representative sample of policy/professional guidelines. A total of 81 papers across SLT and education were included in the review. The papers were scrutinized using a qualitative content analysis. Main Contribution: Although some commonality between perspectives in the literature was identified, differences between the fields dominated. These differences related to how DLD is conceptualized; how children's needs are assessed; which outcomes are prioritized and how best these outcomes can be achieved. We also found differences about what constitutes useful knowledge to guide practice. We suggest that the nature of the differences we identified in the literature may have negative implications for practitioners wishing to collaborate to meet the needs of children with DLD in school. The perspectives of practising SLTs and teachers need to be sought to determine whether the findings from the literature reflect dilemmas in practice. Conclusions: Effective IPC is essential to meet the needs of children with DLD in school; yet, it remains difficult to achieve. Our review of the literature across SLT and education indicates evidence of a lack of shared understanding about DLD. If these differences are also evident in practice, then a conceptual model to support IPC may be warranted.